PEMBERDAYAAN MASYARAKAT ADAT DALIHAN NA TOLU DALAM MEMINIMALISIR KEKERASAN TERHADAP ANAK DI DESA SIMASOM KECAMATAN ANGKOLA JULU - Hennilawati, Hennilawati; Lubis, Mina Syanti; Kamisah, Kamisah; Pohan, Sahruddin (Jurnal ADAM : Jurnal Pengabdian Masyarakat, 2024)
The aim of this Community Service is to provide literacy socialization to the community in Simasom village, Angkola Julu sub-district. The important role of empowering Dalihan Na Tolu community in educating the community about early violence against children, in the sense of the importance of educating children who will become quality future generations so that they can continue the nation's ideals of continuing advanced and civilized independence. Of course, this is a form of effort to prevent the rise of social pathology in society, such as narcotics, free sex, which they have adopted from the increasingly sophisticated flow of technology which inevitably crushes Indonesian society, especially in Angkola Julu sub-district. The target of this research is the Angkola community, namely the younger generation, traditional leaders, and local governments who are related to cultural elements, namely people who still uphold noble values such as mutual respect, love of their homeland, and honesty. So that they are able and have an attitude of wisdom in facing changes in values or norms in the era of globalization whose concept is instantaneous. Children are a nation's assets who will one day maintain, defend and develop the wealth resulting from the nation's struggle. Violence against children will become a phenomenon that will never end, cases and victims always increase every year. Children who are victims of violence will certainly experience physical and psychological trauma, and in the future will have the potential to commit acts of violence (the perpetrator) when they grow up.